THE ANALYSIS OF FEMALE STEREOTYPES IN A VIRTUAL PLAYROOM “FACES OF WOMEN” - Aguaded, Jorge Ignacio (2012)
“Faces of Women” is an educational and playful proposal created for provide resources in the Network for the analysis of female stereotypes in advertising. This article cites various considerations on gender stereotypes and shows the operation of the virtual playroom, which enables users to uncover and do a critical reading of various advertisements. It is a commitment to media literacy for the study of advertising in the media which often present a superficial and patchy image of women compared with men.